Strengthening Adolescent Awareness of Risky Sexual Behavior through Group Guidance Services with Assertive Training Techniques - Nurfarhanah Nurfarhanah; Azahra Hardi Cusinia (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Risky sexual behavior among Indonesian adolescents continues to increase, posing significant risks to health, educational outcomes, and social stability. Information-based educational approaches are often insufficient because they focus primarily on knowledge delivery, without adequately developing psychosocial skills such as assertiveness in managing peer pressure and in establishing personal boundaries. This study employed a quantitative approach using a single-group interrupted time series design with four baseline measurements to examine the effectiveness of group counseling services based on assertiveness training techniques in improving adolescents’ awareness of healthy sexual behavior. Participants consisted of nine 11th-grade students (five females and four males; mean age = 16.8 years) from a public senior high school in Padang, Indonesia. Data were collected using the MESSRA Scale, a 35-item instrument with good internal consistency (Cronbach’s α = 0.87). Measurements were conducted across eight observation points (O1-O8), including four baseline and four post-intervention assessments. The results showed a significant increase in awareness scores from a mean of 101.72 (moderate category) to 128.69 (high category), with a large effect size (r = 0.71). All participants demonstrated improvement, with N-Gain scores categorized as moderate to high. These findings suggest that assertiveness training-based group counseling represents a structured, skill-oriented intervention that can be effectively integrated into school counseling curricula and adolescent reproductive health programs as a preventive strategy. Keywords: adolescents, assertive training, group counseling, healthy sexual behavior, school counseling.